1998
DOI: 10.1007/s001470050474
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral low-dose tacrolimus treatment in liver transplantation

Abstract: Eighty-four adult patients were recruited from four centres in Spain to evaluate the efficacy and safety of low-dose (0.1 mg/kg per day) oral tacrolimus plus corticosteroid immunosuppression in liver transplantation. The median daily dose of tacrolimus was increased during the first 3 weeks of therapy from an initial dose of 0.1 mg/kg per day to a maximum of 0.145 mg/kg per day and was subsequently decreased gradually to a minimum of 0.076 mg/kg per day at 1 year. At 7 days posttransplantation, 87.7% of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
(1 reference statement)
1
11
0
Order By: Relevance
“…1 Incidence of acute rejection is 50% to 75% in patients of cadaveric donor liver transplantation (CLT) under cyclosporine-based immunosuppression 2,3 and is slightly lower in patients treated with tacrolimus (40% to 65%). 4 The targets of activated lymphocytes in acute cellular rejection are bile duct epithelial cells and the endothelium of vein and artery within the liver. The portal infiltrates contain activated lymphoblastoid cells, both B and T cells and plasma cells.…”
mentioning
confidence: 99%
“…1 Incidence of acute rejection is 50% to 75% in patients of cadaveric donor liver transplantation (CLT) under cyclosporine-based immunosuppression 2,3 and is slightly lower in patients treated with tacrolimus (40% to 65%). 4 The targets of activated lymphocytes in acute cellular rejection are bile duct epithelial cells and the endothelium of vein and artery within the liver. The portal infiltrates contain activated lymphoblastoid cells, both B and T cells and plasma cells.…”
mentioning
confidence: 99%
“…In a prospective trial by Steinmiiller et al, no patient treated with tacrolimus developed IDDM after liver transplantation [21]. In contrast, Margarit et al reported that diabetes developed in 33 Yo of liver transplant recipients treated with tacrolimus [13]. In our series, all patients with IDDM responded to conversion, and 15 patients with new-onset IDDM became nondiabetic.…”
Section: Discussionmentioning
confidence: 49%
“…In our study, a few patients had active episodes of infection which was evident by active therapy of antibiotic. Although tremor was common with tacrolimus [44% was reported by Margarit et al (31) in liver transplant patients], there was only one patient who experienced slight tremor in our study, which was recorded as tacrolimus-related in medical notes. The low percentage for the occurrence of tremor may be partly influenced by the nature of the symptom which required self-observation and self-reporting to medical team by patients.…”
Section: Discussionmentioning
confidence: 50%